Advances in waste-to-energy technologies - Singh, Rajeev Pratap; Prasad, Vishal; Vaish, Barkha (CRC Press, 2020)
"As global populations continue to increase, the application of biotechnological processes for disposal and control of waste has gained importance in recent years. Advances in Waste-to-Energy Technologies presents the latest developments in the areas of solid waste management, Waste-to-Energy (WTE) technologies, biotechnological approaches, and their global challenges. It combines biotechnological procedures, sophisticated modeling, and techno-economic analysis of waste, and examines the current need for the maximum recovery of energy from wastes as well as the associated biotechnological and environmental impacts. Features: Presents numerous waste management practices and methods to recover resources from waste using the best biotechnological approaches available. Addresses the challenges, management, and policy issues of waste management and WTE initiatives. Includes practical case studies from around the world. Serves as a useful resource for professionals and students involved in cross-disciplinary and trans-disciplinary research programs and related courses. Discusses the economic and regulatory contexts for managing waste. This book will serve as a valuable reference for researchers, academicians, municipal authorities, government bodies, waste managers, building engineers, and environmental consultants requiring an understanding of waste management and the latest WTE technologies"--